2017
DOI: 10.1186/s40462-017-0101-5
|View full text |Cite
|
Sign up to set email alerts
|

Continuous movement behavior of humpback whales during the breeding season in the southwest Indian Ocean: on the road again!

Abstract: BackgroundHumpback whales are known to undertake long-distance migration between feeding and breeding sites, but their movement behavior within their breeding range is still poorly known. Satellite telemetry was used to investigate movement of humpback whales during the breeding season and provide further understanding of the breeding ecology and sub-population connectivity within the southwest Indian Ocean (SWIO). Implantable Argos satellite tags were deployed on 15 whales (7 males and 6 females) during the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 61 publications
4
33
0
Order By: Relevance
“…These seabed features have in common a relatively shallow depth at their summit (10 to 60 m), surrounding seabed of 1,500 to 2,000 m deep, and guyot shapes with flat summits of a surface ranging from 17 km 2 (Ellet) to 1,800 km 2 (Capel 73 ). Humpback whales have been tracked during the breeding season over similar offshore features, such as Penguin Bank, in Hawaii 39,74 or La Pérouse seamount in the western Indian Ocean 12 . Given their low latitude and/or proximity of these seamounts to known coastal breeding grounds, breeding activities were speculated 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These seabed features have in common a relatively shallow depth at their summit (10 to 60 m), surrounding seabed of 1,500 to 2,000 m deep, and guyot shapes with flat summits of a surface ranging from 17 km 2 (Ellet) to 1,800 km 2 (Capel 73 ). Humpback whales have been tracked during the breeding season over similar offshore features, such as Penguin Bank, in Hawaii 39,74 or La Pérouse seamount in the western Indian Ocean 12 . Given their low latitude and/or proximity of these seamounts to known coastal breeding grounds, breeding activities were speculated 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Humpback whales (Megaptera novaeangliae) were recently discovered to visit seamounts during the breeding season and spring migration period occurring in tropical and subtropical latitudes [10][11][12][13] . Humpback whales seasonally migrate from the polar feeding grounds where they spend the summer, to the tropical breeding grounds where they mate and give birth during the winter.…”
mentioning
confidence: 99%
“…The reasons for such extensive migrations are still debated but could be linked to increased calf fitness in warmer waters of the tropical and subtropical breeding grounds (Clapham, ). Although this hypothesis suggests a direct link between humpback whale life history and water temperature, it remains unclear how sea surface temperature (SST) drives distributions within breeding latitudes, as studies have shown both strong relationships (Bortolotto, Danilewicz, Hammond, Thomas, & Zerbini, ; Guidino, Llapapasca, Silva, Alcorta, & Pacheco, ; Rasmussen et al, ; Smith et al, ) and weak or no effects of this variable (Dulau et al, ; Trudelle et al, ). SST is dynamic, with complex changes through time as it fluctuates on multiple temporal scales (monthly, seasonally, annually) and follows patterns that may be stochastic, cyclic (e.g., El Niño Southern Oscillation [ENSO], Pacific Decadal Oscillation, Antarctic Oscillation [AAO]) or continuous (climate change).…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for such extensive migrations are still debated but could be linked to increased calf fitness in warmer waters of the tropical and subtropical breeding grounds (Clapham, 2000). Although this hypothesis suggests a direct link between humpback whale life history and water temperature, it remains unclear how sea surface temperature (SST) drives distributions within breeding latitudes, as studies have shown both strong relationships (Bortolotto, Danilewicz, Hammond, Thomas, & Zerbini, 2017;Guidino, Llapapasca, Silva, Alcorta, & Pacheco, 2014;Rasmussen et al, 2007;Smith et al, 2012) and weak or no effects of this variable (Dulau et al, 2017;Trudelle et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, greater accuracy (approx. 1 m) is required to elucidate patterns in fine‐scale behaviour (Løkkeborg, Fernö, & Jørgensen, ; Rillahan, Chambers, Howell, & Watson, ), home range movements and habitat selection (Andrews et al, ; Coates, Hovel, Butler, Klimley, & Morgan, ; Espinoza, Farrugia, & Lowe, ), and reproduction (Dulau et al, ).…”
Section: Introductionmentioning
confidence: 99%